Practical Methods to Improve Logistics Processes: A Case Study of Log&Prod Company, Poland - Patrycja GUZANEK; Andrzej SWIDERSKI; Monika KOWALCZUK (Communications of International Proceedings, 2023)
The Covid pandemic had a huge impact on the functioning of enterprises and forced many changes that were introduced to ensure business continuity and ensure survival in these difficult market conditions. An example of such an enterprise is presented in this article. Its aim is to analyse and evaluate logistics processes and identify opportunities for their improvement. It was assumed that it is possible to implement changes in the examined enterprise that would allow for the improvement of logistics processes. The article assumes (research hypothesis) that it is possible to implement changes in the studied enterprise that will allow for the improvement of logistics processes. Even though the situation of the examined company did not require making sudden decisions, introducing improvements was an opportunity to improve the company's financial condition and its position on the market. The article was prepared using research methods such as: analysis and synthesis of available literature, expert interview, document analysis and inference. The article consists of several sections. At the beginning, a literature approach to logistics processes and possible methods of improvements and improvements related to them were presented. Then, the object of work research, i.e. the studied enterprise, was characterized and the selected logistics processes implemented in it were presented. Using appropriate methods, the current condition of the company was diagnosed. The next part presents the improvements implemented by the company and evaluates them. The whole ends with a summary of the changes made in the company and a presentation of the final conclusions.
Keywords: logistics processes; data analysis